2022
DOI: 10.1039/d2dt00706a
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal perovskite Sr6(Co0.8Fe0.2)5O15 as an efficient electrocatalyst towards the oxygen evolution reaction

Abstract: The high overpotential required for the oxygen evolution reaction (OER)—due to the transfer of four protons and four electrons—has greatly hindered the commercial viability of water electrolysis. People have been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
(83 reference statements)
2
11
0
Order By: Relevance
“…Therefore, it is a very important task to synthesize perovskite oxides with specific structural features, including element composition, structure, morphology, crystal phase, and surface defect. In order to achieve the precise control of perovskite element composition, structure, morphology, crystal phase, and surface defects, the synthesis methods of sol–gel, solid phase synthesis, hydrothermal synthesis, and coprecipitation have been used. , We also summarize the advantages and disadvantages of the synthesis methods for perovskite oxides (Table ).…”
Section: Synthesis Methods Of Perovskite Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is a very important task to synthesize perovskite oxides with specific structural features, including element composition, structure, morphology, crystal phase, and surface defect. In order to achieve the precise control of perovskite element composition, structure, morphology, crystal phase, and surface defects, the synthesis methods of sol–gel, solid phase synthesis, hydrothermal synthesis, and coprecipitation have been used. , We also summarize the advantages and disadvantages of the synthesis methods for perovskite oxides (Table ).…”
Section: Synthesis Methods Of Perovskite Catalystmentioning
confidence: 99%
“…In recent years, crystal phase engineering has made great achievements in the field of the OER. ,, At the same time, the unusual phase of materials with different atomic arrangements from the thermodynamically stable phase has attracted great attention. The change of the crystal phase corresponds to the change of the arrangement of atoms in the crystal structure and exhibits different conductivity and activity units, as well as determines its electronic structure and coordination structure.…”
Section: Strategies For Performance Optimization Of Perovskite Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the efficiency of energy conversion in practical applications, a series of OER catalysts have been studied to reduce the reaction energy barrier and improve the reaction rate. Common materials include single metal oxides, [ 5 ] spinel oxides, [ 6 ] perovskite oxides [ 7‐10 ] and hydroxides, [ 11‐12 ] etc . Perovskite, refers to a class of ceramic oxides with the general formula ABO 3 .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The key difference between the cubic and hexagonal structures is that B cations are only connected to corner-sharing points in the cubic structure, while in the hexagonal structure they are connected to face-sharing octahedral sites. Theoretical calculations showed that face-sharing octahedral sites play a vital role in the high OER activity of hexagonal perovskite oxides over cubic ones. Moreover, the ionic size of Ba is greater than that of Sr 2+ and La 3+ , and it has been reported that increasing the size of the A-site cation would increase the O–M bond angle leading to an increase in the electrical conductivity …”
Section: Introductionmentioning
confidence: 99%